City on a hill : a history of American exceptionalism - Van Engen, Abram C., 1981- (Yale University Press, 2020)
In this illuminating book, Abram Van Engen shows how the phrase "City on a Hill," from a 1630 sermon by Massachusetts Bay governor John Winthrop, shaped the story of American exceptionalism in the twentieth century. By tracing the history of Winthrop's speech, its changing status throughout time, and its use in modern politics, Van Engen asks us to reevaluate our national narratives. He tells the story of curators, librarians, collectors, archivists, antiquarians, and often anonymous figures who emphasized the role of the Pilgrims and Puritans in American history, paving the way for the saving and sanctifying of a single sermon. This sermon's rags-to-riches rise reveals the way national stories take shape and shows us how those tales continue to influence competing visions of the country - the many different meanings of America that emerge from its literary past--Publisher description